2013
DOI: 10.7747/jfs.2013.29.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization and Genetic Diversity of Pongamia pinnata (L.) Pierre in Eastern India

Abstract: Biochemical characteristics of 24 Pongamia pinnata genotypes (candidate plus trees) from three agroclimatic zones were estimated and molecular characterization through RAPD markers was done. Various biochemical characters viz. seed oil, total carbohydrates, protein, acid value and Iodine number recorded significant variation among different genotypes. The highest seed oil content was 41.87% while seeds of 14 genotypes recorded above average (32.11%) for the trait. Seed oil and protein content exhibited a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Significant variations in fruit and seed morphological traits were also reported in other studies, viz. Pinus wallichiana (Rawat and Bakshi 2011), Cedrus deodara (Mughal and Thapliyal 2012), Pongamia pinnata (Kumari et al 2013), Jatropha curcas (Khadidiatou et al 2013) and Anthocephalus cadamba (Sudrajat 2016).…”
Section: Variation Of Morphophysiological and Biochemical Traitsmentioning
confidence: 99%
See 4 more Smart Citations
“…Significant variations in fruit and seed morphological traits were also reported in other studies, viz. Pinus wallichiana (Rawat and Bakshi 2011), Cedrus deodara (Mughal and Thapliyal 2012), Pongamia pinnata (Kumari et al 2013), Jatropha curcas (Khadidiatou et al 2013) and Anthocephalus cadamba (Sudrajat 2016).…”
Section: Variation Of Morphophysiological and Biochemical Traitsmentioning
confidence: 99%
“…Bureau of Plant Industry (BPI, 2010) also reported that the main compositions of java olive seeds are fats and protein which are 51.78% and 21.61% respectively. Variation in seed biochemical traits (carbohydrate, protein, fat) were observed in Pongamia pinnata (Jiang et al 2013;Kumari et al 2013) and Jatropha curcas ( (Kumar and Singh 2014). The seed biochemical contents in the selected genotypes also indicate towards some promising candidates for development and utilization in large scale plantation drives.…”
Section: Variation Of Morphophysiological and Biochemical Traitsmentioning
confidence: 99%
See 3 more Smart Citations